Genomic study of the Ket: a Paleo-Eskimo-related ethnic group with significant ancient North Eurasian ancestry - Flegontov, Pavel; Changmai, Piya; Zidkova, Anastassiya; Logacheva, Maria D; Altınışık, N Ezgi; Flegontova, Olga; Gelfand, Mikhail S; Gerasimov, Evgeny S; Khrameeva, Ekaterina E; Konovalova, Olga P; Neretina, Tatiana; Nikolsky, Yuri V; et al. (Scientific reports, 2016)
The Kets, an ethnic group in the Yenisei River basin, Russia, are considered the last nomadic hunter-gatherers of Siberia, and Ket language has no transparent affiliation with any language family. We investigated connections between the Kets and Siberian and North American populations, with emphasis on the Mal'ta and Paleo-Eskimo ancient genomes, using original data from 46 unrelated samples of Kets and 42 samples of their neighboring ethnic groups (Uralic-speaking Nganasans, Enets, and Selkups). We genotyped over 130,000 autosomal SNPs, identified mitochondrial and Y-chromosomal haplogroups, and performed high-coverage genome sequencing of two Ket individuals. We established that Nganasans, Kets, Selkups, and Yukaghirs form a cluster of populations most closely related to Paleo-Eskimos in Siberia (not considering indigenous populations of Chukotka and Kamchatka). Kets are closely related to modern Selkups and to some Bronze and Iron Age populations of the Altai region, with all these groups sharing a high degree of Mal'ta ancestry. Implications of these findings for the linguistic hypothesis uniting Ket and Na-Dene languages into a language macrofamily are discussed.
Keywords: mitochondriální DNA; DNA, Mitochondrial; Inuit; haplotypy; migrace lidstva; genom lidský; genetická variace; fylogeneze; Sibiř; Phylogeny; jazyk (prostředek komunikace); Chromosomes, Human, Y; Haplotypes; Inuité; jednonukleotidový polymorfismus; Phylogeography; Genome, Human; Siberia; Ethnicity; Human Migration; Polymorphism, Single Nucleotide; lidé; Humans; etnicita; fylogeografie; Language; lidský chromozom Y; Genetic Variation